Posted by **Thomas** on Monday, January 9, 2012 at 9:04pm.

I'm not sure if this is even close to how I should solve ths

Rewrite 9x^2 + y^2 + 36x-6y+36 = 0

9(x^2 + 4x+4) + y^2 - 6y+9 = -36 + 36 + 9

9(x+2)^2/9 + (y-3)^2/9 = 1

=(x+2)^2 + (y-3)^2/9 = 1

- Algebra II -
**Steve**, Tuesday, January 10, 2012 at 10:45am
Looks good to me.

## Answer This Question

## Related Questions

- Math (algebra) - Multiply (3x – 7)(3x – 5) A. 9x^2 + 6x + 35 B. 9x^2 + 36x + 35 ...
- Algebra 1 - Okay i don't know how to do this? 13-b 2- 0.5b ------ --------- 6 4 ...
- Algebra 1 - Are these right? xy - 3x - 8y + 24 (3x-y)-(8y+24) 8y+24 4x^2 + 20x...
- algebra - solve the inequality express in interval notation x^4 + 4x^3 - 9x^2 - ...
- algebra - 36x^2 - 49y^2 divided by 6x + 7y meaning 36x^2 - 49y^2 is on top and ...
- ALGEBRA/AM I CORRECT? - THANK YOU! Solve by substitution 3x+6y=6; -6x+y=40 My ...
- algebra - Not sure where to go next. I need to solve this quadratic equation 7x^...
- Algebra - Solve using the elimination method.Show work.If the system has no ...
- Math - 1) Solve: 8x ¨C (6x + 4) = 8 x = -2 2) -7x > 1/15 the solution set is...
- Algebra 2 - Use grouping to solve each of the following equations. 36x+2x^3-36-...

More Related Questions